Diagnostic Challenges and Management Strategies for Superior Sagittal Sinus Thrombosis Induced by Snake Bite Envenomation: A Case Report from Somalia - Ahmed Ahmed A; Elmi AM; Ibrahim IG; Farah Yusuf Mohamud M (Open Access Emergency Medicine)
Abdullahi Ahmed Ahmed,1 Abdinasir Mohamed Elmi,2 Ismail Gedi Ibrahim,2 Mohamed Farah Yusuf Mohamud3,4 1Department of Emergency Medicine, Mogadishu Somali Turkey Training and Research Hospital, Mogadishu, Somalia; 2Department of Radiology, Mogadishu Somali Turkey Training and Research Hospital, Mogadishu, Somalia; 3Faculty of Medicine and Surgery, Mogadishu University, Mogadishu, Somalia; 4Tayo Institute for Research and Development, Mogadishu, SomaliCorrespondence: Mohamed Farah Yusuf Mohamud, Mogadishu University, Talex Street, Hodan District, Mogadishu, Somalia, Tel +252615591689, Email m.qadar59@gmail.comIntroduction: Snakebite is a serious and potentially fatal public health concern, especially in tropical and subtropical regions, leading to severe complications. The World Health Organization (WHO) identified snakebite as a Neglected Tropical Disease (NTD) in 2017 and launched a global campaign in 2019 with the goal of halving the number of snakebite-related deaths and disability cases by half by the year 2030.Case Presentation: A 26-year-old farmer male presented with a snake bite and soon developed neurological complications, including diplopia, seizures, and altered mental status with Glasgow coma scale(GCS) of 11 out of 15. Investigations revealed coagulation abnormalities and magnetic resonance venography showed acute thrombosis of the superior sagittal sinus. The patient was diagnosed with superior sagittal sinus thrombosis. He was admitted to the intensive care unit and treated with anticoagulants to manage the thrombus, prevent further clot formation, and administer seizure medications to control any potential seizures associated with the condition. Moreover, we closely monitored the patient’s condition to ensure effective treatment and to address any complications that may arise. Throughout the next three days, the patient’s health gradually improved due to supportive care. He was extubated and transferred to the general ward. He was discharged after 10 days, having made a full recovery.Conclusion: This case report from Somalia emphasizes the importance of recognizing and managing superior sagittal sinus thrombosis as a rare but life threatening consequence of snake bite envenomation, particularly in resource-limited settings where access to advanced diagnostic and treatment modalities may be limited. If a patient experiences headache, impaired vision or seizures, after a snake bite, it is important to be highly suspicious of cerebral vascular complications including venous sinus thrombosis. Moreover, we recommend that a national study be conducted to identify the prevalent snake species in the region and to determine their specific habitats.Keywords: superior sagittal sinus thrombosis, snake bite, magnetic resonance venography